Appraisal of selection practice and fertility of bull used for frozen semen production in Ethiopia - Tesema, Z.; Besufkad, S.; Kassahun, D.; Deribe, B.; Abebe, A.; Zewdie, T.; Araya, A.; Yitagesu, E.; Alemayehu, L.; Agegnehu, B.; Gizaw, Solomon (Wiley, 2025)
This study aimed to evaluate the selection practice and fertility of bulls recruited and used for frozen semen production. Data were collected through key informant interviews and longitudinal measurement of fertility and morphological traits of bulls. The preservice morphology and fertility data were collected from 2011 to 2022 from 193 candidate bulls. About 908 records of 68 bulls were used to evaluate the semen quality of bulls used for frozen semen production. The result of this study revealed that private small-scale dairy farms (71.7%), along with research centers (18.87%), constituted the major source of improved bulls utilized for semen production. Bulls were not selected based on their estimated breeding value, but rather based on the milk yield performance of their dam, conformation, growth, and health status. Bulls were extensively utilized for long periods, up to six years, without knowing their genetic superiority. Bulls selected for semen production had good semen volume, concentration, mass motility, individual motility, and live cells, which were higher than the minimum standard. The results of this study indicated that bull selection for frozen semen production was as per the predefined bull selection standard in terms of fertility and morphological traits. However, further progeny and pedigree tracing must be carried out on selected superior bulls. The absence of selection for genetically superior bulls based on estimated breeding value, an extended service length, overutilization of few bulls, and absence of a recording system may cause inbreeding and adversely affect the productivity, fitness of crossbred animals, and sustainability of dairy cattle production.